Efektifitas Komunikasi Keselamatan dan Kesehatan Kerja (K3) dalam Mencegah Penularan Covid-19 di PLN UPDL Semarang - Tri Sakti Adiwibowo (Sekolah Tinggi Teknik PLN, 2020)
Abstract The Covid-19 pandemic has affected the activities of the PLN UPDL Semarang as the provider of education and training at PLN to prevent the spread of the Covid-19 outbreak by arranging learning schedules and methods, implementing New Habit Adaptation (IMR) in the form of wearing masks, maintaining distance, washing hands with soap, and equip sufficient Personal Protective Equipment (PPE). This effort must be communicated to all workers as a form of compliance with the implementation of the Work Safety Management System (SMK3) in accordance with Government Regulation number 50 of 2012. The purpose of this study was to determine the effectiveness of communication in the UPDL Semarang environment in preventing Covid-19 transmission. In this study the authors used survey, observation, interview methods to obtain preliminary data. Furthermore, these data are evaluated and confirmed with secondary data related to the impact of communication. From this study, it was found that occupational safety and health communication in an effort to prevent the transmission of Covid-19 in the PLN UPDL Semarang environment reached an effectiveness of 78.29%. Things that need to be improved in this communication are the use of brochure / poster communication media